A Capabilities Perspective of Bottom of Pyramid for Multinational Corporations – An Exploratory Study - Umar, Shahzad (2012)
Purpose: To identify the organizational capabilities needed by organizations within the context of BoP and determine their impact on Human Resources strategy of these companies. Research Design: A number of published pieces of work on BoP, innovation, corporate entrepreneurship and human resources were reviewed and critiqued. The findings from literature review were put in the form of a preliminary framework which was used to conduct field research to test its applicability in BoP space. Findings / Value: This study first reviews all the important activities and agents, both internal and external to an organization and then establishes ―Innovation‖ and ―Corporate Entrepreneurship‖ as the critical capabilities needed for effective strategic orientation of BoP. To finish, this research goes the last mile by providing a completely new dimension to BoP literature by highlighting the implications of critical BoP capabilities on the role of human resources function within an organization. HR departments and HR professionals can use BoP as an opportunity to initially help define the strategic intent with in the organization for BoP and then lead from front by putting in place a comprehensive HR strategy, organizational structure, recruiting, training, rewarding and recognition practices for the organization to successfully address BoP challenge.